Arbitration in construction industry in Malaysia - 454449 Nor Azmi Bakhary (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Master of Engineering (Civil-Construction and Management)) - Universiti Teknologi Malaysia, 2003